1995
DOI: 10.1159/000196447
|View full text |Cite
|
Sign up to set email alerts
|

A Way to Select on Clinical Grounds Patients with High Risk for Pulmonary Embolism: A Retrospective Analysis in a Nested Case-Control Study

Abstract: We studied 196 patients with suspicion of pulmonary embolism (PE), subsequently confirmed in 98 by positive pulmonary angiography and excluded in 98 by normal or near-normal perfusion lung scan. Patients had a clinical questionnaire for history, and, soon after, a radiograph, blood gas analysis, and an ECG. Clinical and instrumental signs were matched in patients with confirmed and unconfirmed PE to find those more frequent in embolic patients and, thus, more characteristic of PE. The following were: previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…First, sample size was probably insufficient given the low prevalence of AF in case of PE. Second, all but one study [15] suffered from a lack of adjustments for main confounding factors. Finally, as these studies included patients with PE suspicion only, selection bias could have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…First, sample size was probably insufficient given the low prevalence of AF in case of PE. Second, all but one study [15] suffered from a lack of adjustments for main confounding factors. Finally, as these studies included patients with PE suspicion only, selection bias could have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Both RV diameter and the end-diastolic RV/LV ratio had a signifi cant association with the diameter of right descending pulmonary artery on chest X-rays. An enlarged right descending pulmonary artery was matched in patients with confi rmed and unconfi rmed PE and has been more frequently seen in embolic patients in literature [24]. Previously it has also been shown that there is an association between the diameter of the right descending pulmonary artery and pulmonary hypertension as revealed by right heart catheterization and by echocardiography [17,25].…”
Section: Discussionmentioning
confidence: 95%
“…In these case matched patients we sought evidence, by case note review, of the presence of major risk factors for venous thromboembolism. [2][3][4][5] The presence of risk factors for thromboembolism was compared in HIV infected patients with and without pulmonary embolism by means of an odds ratio using a Mantel-Haenszel estimate. 8…”
Section: Methodsmentioning
confidence: 99%
“…1 Several major risk factors for venous thromboembolism have been identified including recent abdominal surgery, disseminated malignancy, previous venous thromboembolism, immobilisation for more than 1 week, disabling cardiorespiratory disease, age >40 years, and thrombotic disorders. [2][3][4][5] In contrast, reports of pulmonary embolism in HIV infected individuals are scarce, despite descriptions of the hypercoagulable state due to HIV associated lupus anticoagulant, anticardiolipin antibodies, and protein S deficiency. 6 Diagnosis of acute pulmonary embolism may be diYcult and usually relies on a strong clinical history with supportive imaging, most often a ventilation/perfusion (V/Q) scan.…”
Section: Introductionmentioning
confidence: 99%